(untitled) (Nashville, TN Abingdon, 2000)
Contents: v.11 : 2 Corinthians, Galatians, Ephesians, Philippians, Colossians, 1-2 Thessalonians, 1-2 Timothy, Titus, Philemon. Includes bibliographical references, maps, charts, etc.
Full texts and critical notes of the New International Version and New Revised Standard Version of the Bible in parallal columns.
Keywords: Bible -- commentaries